2013
DOI: 10.1161/circulationaha.113.001719
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Cardiac Magnetic Resonance Imaging and Spectroscopy Reveal a High Burden of Myocardial Disease in HIV Patients

Abstract: Background— HIV infection continues to be endemic worldwide. Although treatments are successful, it remains controversial whether patients receiving optimal therapy have structural, functional, or biochemical cardiac abnormalities that may underlie their increased cardiac morbidity and mortality. The purpose of this study was to characterize myocardial abnormalities in a contemporary group of HIV-infected individuals undergoing combination antiretroviral therapy. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
149
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(166 citation statements)
references
References 27 publications
14
149
1
2
Order By: Relevance
“…We have previously reported, in a cohort of asymptomatic treated patients with HIV, findings of increased cardiac steatosis and myocardial regional fibrosis although these findings did not fully explain the extent of myocardial dysfunction. 10 Our observations have been replicated by Thiara et al 11 In this study, we used our previous cohort and an additional 66 subjects, including a group naive to ART, and we investigated whether there is an association between myocardial inflammation in subjects with HIV and cardiac pathology.…”
Section: Ntusi Et Al Hiv-1-associated Cardiovascular Diseasesupporting
confidence: 55%
See 1 more Smart Citation
“…We have previously reported, in a cohort of asymptomatic treated patients with HIV, findings of increased cardiac steatosis and myocardial regional fibrosis although these findings did not fully explain the extent of myocardial dysfunction. 10 Our observations have been replicated by Thiara et al 11 In this study, we used our previous cohort and an additional 66 subjects, including a group naive to ART, and we investigated whether there is an association between myocardial inflammation in subjects with HIV and cardiac pathology.…”
Section: Ntusi Et Al Hiv-1-associated Cardiovascular Diseasesupporting
confidence: 55%
“…We previously published the initial results from this study and have expanded on these results by adding 66 subjects, including 13 patients with HIV naive to ART. 10 Subjects included in the study were older than 18 years and had a confirmed diagnosis of HIV. Exclusion criteria included contraindications to CMR, nonsinus rhythm, known CVD (previous myocardial infarction, previous myocarditis, heart failure, arrhythmia, or other chronic cardiac conditions), a history of hepatitis C or injection drug use, renal impairment (estimated glomerular filtration rate, <30 mL/min), impaired liver function (alanine aminotransferase greater than twice the upper limit of normal), a woman who was pregnant, lactating or planning a pregnancy, and known hypersensitivity to gadolinium.…”
Section: Study Populationmentioning
confidence: 99%
“…63,66 T1 mapping helped to unravel the low-grade myocardial inflammation and improved understanding of subclinical course of cardiac involvement in patients with systemic inflammation, chronic infection, and drug-induced cardiotoxicity. 19,[67][68][69][70] These occur in the absence of overt cardiac dysfunction or abnormalities on the currently used CMR sequences, adding potential tools of screening in populations at high risk of cardiomyopathy and HF.…”
Section: T1 Mapping In Myocardial Inflammationmentioning
confidence: 99%
“…Myocardial fibrosis may play a key role; it is a key pathophysiological driver for the development of cardiac arrhythmias, and both the presence and the extent of myocardial fibrosis are predictors of ventricular arrhythmias 15, 18, 19, 20. At baseline, PHIV without HF have both an increase in the presence and extent of myocardial fibrosis 21, 22. For example, Holloway and colleagues detected late gadolinium enhancement, replacement myocardial fibrosis on MRI, in 76% of PHIV compared with 13% of controls 21.…”
Section: Discussionmentioning
confidence: 99%
“…At baseline, PHIV without HF have both an increase in the presence and extent of myocardial fibrosis 21, 22. For example, Holloway and colleagues detected late gadolinium enhancement, replacement myocardial fibrosis on MRI, in 76% of PHIV compared with 13% of controls 21. In a complementary study, Thiara and colleagues found an increased extent of diffuse myocardial fibrosis among PHIV 23.…”
Section: Discussionmentioning
confidence: 99%